Attribute-Based Access Control. - Hu, Vincent (Artech House information security and privacy series., 2018)
This comprehensive new resource provides an introduction to fundamental Attribute Based Access Control (ABAC) models. This book provides valuable information for developing ABAC to improve information sharing within organizations while taking into consideration the planning, design, implementation, and operation. It explains the history and model of ABAC, related standards, verification and assurance, applications, as well as deployment challenges.n nReaders find authoritative insight into specialized topics including formal ABAC history, ABAC's relationship with other access control models, ABAC model validation and analysis, verification and testing, and deployment frameworks such as XACML. Next Generation Access Model (NGAC) is explained, along with attribute considerations in implementation. The book explores ABAC applications in SOA/workflow domains, ABAC architectures, and includes details on feature sets in commercial and open source products. This insightful resource presents a combination of technical and administrative information for models, standards, and products that will benefit researchers as well as implementers of ABAC systems in the field.